المادة التعليمية على أساس المدخل السياقي (بحث تطويري لدى طلبة قسم الاقتصاد الشرعي بجامعة التنوير الإسلامية بوجونغارا) - أحمد مصطفى; نور ليلى رحمواتي (Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2017)
The objectives of the study is to (1) develop Arabic learning material that uses contextual approach for the students of Islamic Economy department in the book product, (2)  know the validity and the feasibility of the book by using contextual approach for the students of Islamic Economic department. The research used research and development (R and D) method using ADDIE model. The data consisted of qualitative and quantitative, while the data instrument used questionaire and interview. The data were  analyzed using descriptive and qualitative statistics. The findings showed that the book product is valid and feasible with Arabic learning materials, concerning and related to the expert analysis and the user test. Keywords: Arabic learning material, contextual approach, validity and feasibility